2019
DOI: 10.1016/j.dadm.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific incident dementia in patients with central nervous system trauma

Abstract: Introduction Despite evidence that central nervous system (CNS) trauma, including traumatic brain injury and spinal cord injury, can cause sustained neurocognitive impairment, it remains unclear whether trauma-related variables are associated with incident dementia independently of other known risk factors. Methods All adults without dementia entering the health-care system with diagnoses of CNS trauma were examined for occurrence of dementia. All trauma-related variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…To better understand cognitive impairments stemming from TBI, a number of cohort studies identified groups at risk of post‐injury cognitive decline 7 and reported worse cognitive outcomes in those with lower socioeconomic standing, system level comorbidities, more severe TBI, or concussive nature of injury. A recent longitudinal study confirmed these risk factors, and also found that comorbid spinal cord injury (SCI) increases the risk of incident dementia in both men and women with TBI across injury severities, even after controlling for depression, sleep disorders, and other previously noted risk factors 8 . Spinal cord injury in TBI is expected to disrupt conduit functions of tracts going to and from higher centers in a variety of ways, manifesting in different clinical presentations, heterogeneous abnormalities, including those concerning cognition.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…To better understand cognitive impairments stemming from TBI, a number of cohort studies identified groups at risk of post‐injury cognitive decline 7 and reported worse cognitive outcomes in those with lower socioeconomic standing, system level comorbidities, more severe TBI, or concussive nature of injury. A recent longitudinal study confirmed these risk factors, and also found that comorbid spinal cord injury (SCI) increases the risk of incident dementia in both men and women with TBI across injury severities, even after controlling for depression, sleep disorders, and other previously noted risk factors 8 . Spinal cord injury in TBI is expected to disrupt conduit functions of tracts going to and from higher centers in a variety of ways, manifesting in different clinical presentations, heterogeneous abnormalities, including those concerning cognition.…”
mentioning
confidence: 71%
“…All adult (≥18 years) Ontario residents who had received a diagnosis of CNS trauma 8 in an emergency department or acute care unit between April 1, 2002 and March 31, 2016 were identified using previously validated case definitions based on health administrative data 29,30 . The date of the first TBI diagnosis following open or closed injury (based on whether there was breach of the integrity of the cranial vault) was defined as the index date that marked the beginning of the study period for each patient.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations